Resveratrol directly controls the activity of neuronal ryanodine receptors at the single channel level - Kraus, JG (Mol Neurobiol, 2019)
Calcium ion dyshomeostasis contributes to the progression of many neurodegenerative diseases and represents a target for the development of neuroprotective therapies (1–3). Dysfunctional ryanodine receptors contribute to calcium ion dyshomeostasis and potentially to the pathogenesis of neurodegenerative diseases by generating abnormal calcium ion release from the endoplasmic reticulum (4–5). Since ryanodine receptors share functional and structural similarities with potassium channels (6), and small molecules with anti-oxidant properties, such as resveratrol (3,5,4′-trihydroxy-trans-stilbene), directly control the activity of potassium channels (7–12), we hypothesized that trans-resveratrol can modulate intracellular calcium signaling through direct binding and functional regulation of ryanodine receptors. The goal of our study was to identify and measure the control of ryanodine receptor activity by trans-resveratrol. Mechanisms of calcium signaling mediated by the direct interaction between trans-resveratrol and ryanodine receptors, were identified and measured with single channel electrophysiology. Addition of trans-resveratrol to the cytoplasmic face of the ryanodine receptor increased single channel activity at physiological and elevated pathophysiological cytoplasmic calcium ion concentrations. The open probability of the channel increases after interacting with the small molecule in a dose-dependent manner, but remains also dependent on the concentration of its physiological ligand, cytoplasmic free calcium ions. This study provides the first evidence of a direct functional interaction between trans-resveratrol and ryanodine receptors. Such functional control of ryanodine receptors by trans-resveratrol as a novel mechanism of action could provide additional rationales for the development of novel therapeutic strategies to treat and prevent neurodegenerative diseases.